Critical Zone Structure Under a Granite Ridge Inferred From Drilling and Three‐Dimensional Seismic Refraction Data. Issue 6 (16th June 2018) - Flinchum, Brady A.; Steven Holbrook, W.; Rempe, Daniella; Moon, Seulgi; Riebe, Clifford S.; Carr, Bradley J.; Hayes, Jorden L.; St. Clair, James; Peters, Marc Philipp
Abstract: Observing the critical zone (CZ) below the top few meters of readily excavated soil is challenging yet crucial to understanding Earth surface processes. Near‐surface geophysical methods can overcome this challenge by imaging the CZ in three dimensions (3‐D) over hundreds of meters, thus revealing lateral heterogeneity in subsurface properties across scales relevant to understanding hillslope erosion, weathering, and biogeochemical cycling. We imaged the CZ under a soil‐mantled ridge developed in granitic terrain of the Laramie Range, Wyoming, using data from five boreholes and a 3‐D volume (970 by 600 by 80 m) of seismic velocities generated by ordinary kriging of 25 two‐dimensional seismic refraction transects. The observed CZ structure under the ridge broadly matches predictions of two recently proposed hypotheses: the uppermost surface of weathered bedrock is consistent with subsurface weathering driven by bedrock drainage and subsurface topography defining the top of unweathered protolith is consistent with fracturing predicted from topographic and regional stresses. In contrast, differences in slope aspect along the ridge are too subtle to explain observed variations in regolith structure. Our observations suggest that multiple processes, each of which may dominate at different depths, work in concert to regulate deep CZ structure. Key Points: Seismic refraction, drilling, and geostatistics provide insight into deep critical zone structure at unprecedented scales Multiple processes conspire to influence variations in subsurface fracturing and weathering Variability in saprolite and fractured bedrock thickness is not readily explained by models of critical zone evolution